Pengaruh Persepsi Manfaat, Kemudahan, Risiko, dan Sosial Terhadap Minat dengan Sikap Sebagai Mediasi : Studi pada Pengguna Mobile Banking Livin’ by Mandiri di Pemalang - Putri Agustya; Santi Suciningtyas; Tri Handayani; Victor Prasetya (BADAN PENERBIT STIEPARI PRESS, 2025)
The aim of this research is to examine and describe the extent of the impact of the variables Perceived Usefulnessss, Perceived Ease of Use, Risk, and Social Influence on Interest in Using through the mediation of the Attitude Toward Using variable. The population studied was Livin' by Mandiri mobile banking users in Pemalang, using a research sample of 100 respondents selected through purposive sampling and accidental sampling methods. Information was obtained by observation, filling out a questionnaire using Google Form, and studying relevant literature. Data analysis used IBM SPSS Statistics 25 with various statistical tests, such as instrument validity and reliability tests, classical assumption tests, multiple linear regression analysis, coefficient of determination (R2), t test, path analysis, and the Sobel test which was analyzed using the Sobel test calculator. The research results found that there was a significant direct impact on the variables Perceived Usefulnessss (X1), Perceived Ease of Use (X2), Risk (X3), Social Influence (X4), and Attitude Toward Using (Z) with Interest in Using (Y). Apart from that, Attitude Toward Using (Z) plays a significant role as a link to the indirect impact of these variables on Interest in Using (Y). Keywords: Perceived Usefulnessss; Perceived Ease of Use; Risk; Social Influence; Attitude Toward Using; and Interest in Using.